Laser surface alloying fabricated porous coating on NiTi shape memory alloy - 张松 张春华 文效忠 刘常升 (Transactions of Nonferrous Metals Society of China, 2007)
Laser surface alloying technique was applied to fabricate a metallic porous coating on a solid NiTi shape memory alloy. By laser surface alloying a 40%TiH2-60%NiTi powder mixture on the surface of NiTi alloy using optimized laser process parameters, a porous but crack-free NiTi layer can be fabricated on the NiTi substrate. The porous coating is metallurgically bonded to the substrate NiTi alloy. The pores are uniformly distributed and are interconnected with each other in the coating. An average pore size of less than 10μm is achieved. The Ni content of the porous layer is much less than that of the original NiTi surface. The existence of the porous coating on the NiTi alloy causes a 37% reduction of the tensile strength and 55% reduction of the strain as compared with the NiTi alloy. Possible biomedical or other applications for this porous surface with good mechanical strength provided by the substrate are prospective.